SMS/text messaging virtual reference service @ De La Salle University - Odsinada, Yolanda F. (Animo Repository, 2012)
The service has already been running on for twelve months or forty full weeks of classes from the time it was put into operation. To date, there has no study conducted on reference service through SMS/text message in the local setting and in particular in the De La Salle University. This paper reports on the study designed to explore the status of the De La Salle University SMS/Text message reference service.